Mobile device forensics : - Μπαρμπάτσαλου, Κωνσταντία (2013)
Mobile Forensic is an interdisciplinary eld consisting of techniques applied to a bigvariation of handheld device types. A great number of researches have been conducted,concerning various mobile operating systems, data acquisition types and retrieved datatypes. This paper aims to provide an adequate view of the eld, by reviewing and presen-ting a detail overview of the actions taken throughout the last seven years. A schematictimeline of the most signi cant studies will be designed, in order to provide researcherswith a quick but satisfying way of observing the trends within the eld. This will as wellbe an analytic progress report, concerning the evolution of mobile forensics. Since thereis a lack of standardization problem, the research can set the foundations for a commonframework proposal. Technology concerning mobile devices is evolving in a rapid scaleand disciplines will succumb to changes frequently. A strong fundamental infrastructurethough will serve to quick and eff ective adaptation.